THE DEVELOPMENT of DIGITAL AUDIOVISUAL MEDIA KLICKS DEUTSCH BASED on ARTICULATE STORYLINE on RUND UMS ESSEN THEME in LEARNING GERMAN - Baiq Tsania Avi Salwa Issabella; Lilis Afifah; Audrey Gabriella Titaley (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
This research aimed to develop Klicks Deutsch, a digital audiovisual media for learning German. Klicks Deutsch was created using an interactive media creator application called Articulate Storyline. The material presented in this media is Rund ums Essen (about food) for Basic Competency 3.2 and 4.2 in curriculum 2013. Moreover, this research was a Research and Development (R&D) type using the ADDIE development model which consists of five phases, namely analysis, design, development, implementation and evaluation. The data were collected using questionnaires. After being validated by the experts, Klicks Deutsch was then implemented on 26 students of grade XI Language at SMAN 8 Malang. Finally, the results of the assessments show that Klicks Deutsch has reached a quite valid qualification. In other words, this media is liable to be used as a media for German learning, since it gained 85% score from material expert, 95.6% from media expert and 91.4% from student as users.